Engaging Preschool Children With Severe and Multiple Disabilities Using Books and iPad Apps. Issue 4 (October 2016) - Kemp, Coral; Stephenson, Jennifer; Cooper, Megan; Hodge, Kerry
Abstract : A single subject multiple treatment design was used to compare the engagement of 3 preschool children with severe and multiple disabilities, using 2 different stimuli: picture books and iPad apps matched for theme and content. Two of the 3 children had diagnoses of autism spectrum disorder in addition to their other disabilities. Sessions for each child were guided by trained facilitators who were staff working in the inclusive childcare settings attended by the children. Sessions were video recorded and later coded using a 5-second interval recording system. Visual inspection of the data indicated that 1 child was equally engaged with both media, while the 2 with diagnosed autism spectrum disorders were better engaged with the iPad apps. These results are discussed in relation to the potential of technology to engage children with high support needs and autism spectrum disorder with a view to enhancing their engagement in inclusive early childhood settings.